Metagenomic analysis of black-stained plaques in permanent dentition. (August 2021) - Çelik, Zeynep Ceren; Çakiris, Aris; Yanıkoğlu, Funda; Abacı, Neslihan; Ekmekçi, Sema Sırma; Ilgın, Can; Çelik, Halil; Tağtekin, Dilek
Highlights: Black stain has multimicrobial etiology and related with low caries. Capnocytophaga, Corynebacterium, Neisseria spp. were higher in black stain. Next Generation Sequencing helps to detect complex oral microbiome. Abstract: Objectives: We aimed to determine the aetiologic agent responsible for black staining of permanent dentition using next-generation sequencing and determine the relationship between caries and black stains. Materials and methods: A total of 52 systemically healthy patients with black-stained and caries-free (n = 13), black-stained and carious (n = 13), black stain-free and caries-free (n = 13), and black stain-free and carious (n = 13) teeth were enrolled in the study. The International Caries Detection and Assessment System (ICDAS II) was used for caries classification. Between 08:00 and 10:00, supragingival plaque samples were collected after a minimum of 8–12 h of accumulation and DNA samples were isolated. The samples were processed using the ZymoBIOMICS™ Service. Bioinformatics analysis was performed using mothur at usegalaxy.org. Data were analysed statistically using the Pearson chi-square and Fisher tests. Results: The number of caries-free teeth (ICDAS 0, 1, and 2) was significantly higher in patients with black stains (p = 0.007). Capnocytophaga (4.8 %), Corynebacterium (3.9 %), and Neisseria (5.4 %) species were the most abundant among all black-stained plaques (carious and caries-free) (p < 0.05). Capnocytophaga (10.8 %), Cardiobacterium (3.6 %), and Rothia (1.72 %) species were detected in the black-stained plaques of caries-free patients (p < 0.05). Conclusion: This study is one of the first studies examining the microbial composition of dental plaques with black staining in carious and caries-free adult patients using next generation sequencing technology. In the presence of black staining, plaques have an ultimate complex microbial structure. A lower caries burden was noted in the presence of black staining.